About involvement of peroxisome-proliferator-activated receptor gamma in mechanism of antiulcer action of melanin isolated from antarctic yeasts - Kukharskyy, V. M.; Chyizhanska, N. V.; Tsyryuk, O. I. (Ukrainian Antarctic Journal, 2009)
In acute experiments on 55 white rats we investigated one of the possible mechanisms of cytoprotective action of melanin via activation of peroxisome proliferator-activated receptors gamma. It was established that immobilization stress by Groisman and Karevina evoked in gastric mucosa the formation of ulcers, erosions and hemorrhages. Melanin in dose 5 mg/kg defended gastric mucosa against development of injuries evoked by stress. Irreversible selective antagonist of peroxisome proliferator-activated receptors gamma GW9662 in dose 1 mg/kg removed the cytoprotective action of melanin on formation of stress injuries. We concluded that antistress action on gastric mucosa in rats completely or partly is governed by activation of peroxisome proliferator-activated receptors gamma.